Asignación de Ancho de Banda Dinámico en Arquitectura de Red Óptica Pasiva sobre GigaBit (GPON) - López Sarmiento, Danilo Alfonso; Gelvez García, Nancy Yaneth (Ingeniería, 2007)
This paper aims to present an alternative to improve the quality of service offered by the networks PONs ensuring an allocation of bandwidth commensurate with the service level agreements offered by the ISP. Through the simulation, discusses the effectiveness of applying techniques of wave division multiplexing in these networks, allowing that the downstream and upstream capacity, will be tailored to the needs of the users, compared to the capabilities of other techniques such as TDM-PON